Blind spots in health perception: the underestimated role of social connection for health outcomes - Andrew Scot Proctor; Julianne Holt-Lunstad (BMC Public Health)
Abstract Background Robust evidence indicates that having few or poor-quality social connections is associated with poorer physical health outcomes and risk for earlier death (Snyder-Mackler N, Science 368, 2020; Vila J, Front Psychol 12:717164, 2021). Aim This study sought to determine whether recent attention on social connection and loneliness brought on by the COVID-19 pandemic may influence risk perception and whether these perceptions were heightened among those who are lonely. Methods Two waves of online survey data were collected. The first included data from 1,486 English-speaking respondents in the US, UK, and Australia, and a second sample of 999 nationally representative US adults, with a final sample of 2392 respondents from the US and UK. Results Perceptions of risk have remained consistent, underestimating the influence of social factors on health outcomes and longevity, even among respondents who reported moderate-to-severe levels of loneliness. Conclusions Despite heightened awareness and discourse during the COVID-19 pandemic, public perception in the US and UK continues to significantly underestimate the impact of social factors on physical health and mortality. This underestimation persists regardless of individual loneliness levels, underscoring the need for enhanced public education and policy efforts to recognize social connection as a crucial determinant of health outcomes.